Effect of Mother Tree, Sowing Method, Heat Treatment and Rainfall Distribution on Germination Percent of Kusum seeds (Schleichera oleosa (Lour .) Oken.) - Ghosal, S; Chowdhury, Arnab Roy (Indian Forester, 2023)
Lac is the source of natural resin of animal origin. Best quality kusmi lac is produced in kusum trees (Schleichera oleosa). Plantation raising face difficulty, since germination of seeds is unpredictable. Effect of several factors like mother tree, sowing method, heat treatment and rainfall distribution were examined through different experiments during 2014-18 in Institute Research Farm, ICAR-Indian Institute of Natural Resins and Gums, Ranchi. Trees receiving more than 40 percent exposure and having 5.25 m branch length could achieve as high as 67 percent germination. Results evidenced that germination percent increases with passage of time. Heat treatment of seed proved that exposure of seeds to 50oC temperature for 3-6 hours can increase germination percent to the tune of 37 to 67 percent in comparison to normal condition. Analysis of rainfall data during the experimental period suggested that rainfall in the month of May could be crucial in dictating seed set and germination percent of kusum. It was estimated that a minimum of 63 mm of rainfall is required in May for satisfactory seed germination.